2020
DOI: 10.1175/bams-d-19-0051.1
|View full text |Cite
|
Sign up to set email alerts
|

The Total Solar Eclipse of 2017: Meteorological Observations from a Statewide Mesonet and Atmospheric Profiling Systems

Abstract: A total solar eclipse traversed the continental United States on 21 August 2017. It was the first such event in 99 years and provided a rare opportunity to observe the atmospheric response from a variety of instrumented observational platforms. This paper discusses the highquality observations collected by the Kentucky Mesonet (www.kymesonet.org), a research-grade meteorological and climatological observation network consisting of 72 stations and measuring air temperature, precipitation, relative humidity, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…This event was particularly remarkable in terms of measurements performed during solar eclipses since ah hoc observing campaigns were organized to increase the number as well as temporal and geographical density of observations (Dodson et al, 2019). Overall, more than 170,000 surface temperature and 40,000 cloud cover observations were obtained, resulting in a mean eclipse-related cooling among the observing sites of 3.5 • C. Changes in vertical profiles of temperature and water vapor density were also documented for this eclipse by Mahmood et al (2020).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This event was particularly remarkable in terms of measurements performed during solar eclipses since ah hoc observing campaigns were organized to increase the number as well as temporal and geographical density of observations (Dodson et al, 2019). Overall, more than 170,000 surface temperature and 40,000 cloud cover observations were obtained, resulting in a mean eclipse-related cooling among the observing sites of 3.5 • C. Changes in vertical profiles of temperature and water vapor density were also documented for this eclipse by Mahmood et al (2020).…”
Section: Introductionmentioning
confidence: 97%
“…Relatively few studies exist prior to the February 16, 1980 eclipse, and after then the highest number of articles is found for the August 1999 TSE that affected parts of Europe and southern Asia. More recently, several studies have analyzed the TSE which took place over North America during August 2017 (e.g., Dodson et al ., 2019; Mahmood et al ., 2020), which was the first to occur there in almost a century. This event was particularly remarkable in terms of measurements performed during solar eclipses since ah hoc observing campaigns were organized to increase the number as well as temporal and geographical density of observations (Dodson et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Moon is in a position where it blocks the light from the Sun, the quick onset of the darkness induces a sudden drop in temperature of the air and generates local circulation near the Earth's surface (Clayton 1901;Aplin et al 2016;Clark et al 2016;Eugster et al 2017;Turner et al 2018;Mahmood et al 2020). Wang and Liu (2010) first examined the FORMOSAT-3/COSMIC (Constellation Observing System for Meteorology, Ionosphere, and Climate) radio occultation (RO) temperature profiles during the 22 July 2009 total solar eclipse and found that atmospheric response to the solar eclipse is not as simple as a cooling of the whole atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The number of scientists has postulated that UV and blue light may contribute to retinal ageing and macular degeneration and UV and deep blue light have been shown to be damaging to the retina in laboratory studies. Epidemiological studies to date have not demonstrated any clear relationship, except possibly for some severe forms of the disease that seem associated with a history of greater blue light exposure (Kastendeuch et al 2016;Lee et al 2018;Liu et al 2020;Mahmood et al 2020).…”
Section: Introductionmentioning
confidence: 99%